Strategy For Optimizing The Potential Of Gomara Swiss Natural Tourism Through Swot Analysis For The Economic Empowerment Of The Local Community In Labuhan Batu Utara Regency - Ratnasari, Dewi; Yusrizal, Yusrizal; Syahbudi, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
This research aims to identify internal and external factors and formulate strategies for optimizing the potential of Gomara Swiss Nature Tourism through a SWOT analysis for empowering the local community's economy in Labuhan Batu Utara Regency. A qualitative approach with a descriptive and analytical case study design is employed. Primary data were collected through participatory observation, in-depth interviews, FGDs, and SWOT questionnaires, while secondary data were obtained from literature studies and related documents. Data analysis was carried out using qualitative descriptive, IFAS, EFAS, and Rangkuti's (2018) SWOT method. The findings reveal that the development of Gomara Swiss Nature Tourism has a positive impact on the local community's economy, such as increased income, the growth of micro-enterprises, and the absorption of local labor. The main strategies recommended include gradual growth through digital promotion and facility development, internal strengthening via community empowerment and local HR training, sustainable product development with a halal ecotourism concept, institutional and partnership reinforcement, and risk mitigation for environmental and socio-cultural sustainability. These strategies aim to foster controlled growth of Gomara Swiss Nature Tourism while maximizing economic benefits for the local community and preserving the environment and local culture. Collaborative efforts from the government, private sector, and community are needed to implement these strategies effectively.